2009
DOI: 10.1517/14656560903382622
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapy of actinic keratosis

Abstract: Actinic keratosis (AK) represents the initial intraepidermal manifestation of abnormal keratinocyte proliferation with the potential of progression to squamous cell carcinoma (SCC). When in limited numbers, clinically visible AKs are treated individually with ablative and/or surgical procedures (lesion-directed treatment), while multiple and sublinical AKs are treated with field-directed therapies that use ablative, nonablating and other topically applied treatment modalities. Owing to difficulties in predicti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 133 publications
1
13
0
1
Order By: Relevance
“…Here we show, using the hairless SKH-1/hr mouse model, that field-directed treatment (Berman et al, 2009;Jorizzo et al, 2010;Feldman and Fleischer, 2011) of precancerous chronically UVBirradiated skin with ingenol mebutate significantly reduced the number of skin lesions that subsequently developed. Ingenol mebutate treatment also significantly reduced the number of mutant p53 patches present in the skin.…”
Section: Introductionmentioning
confidence: 59%
See 1 more Smart Citation
“…Here we show, using the hairless SKH-1/hr mouse model, that field-directed treatment (Berman et al, 2009;Jorizzo et al, 2010;Feldman and Fleischer, 2011) of precancerous chronically UVBirradiated skin with ingenol mebutate significantly reduced the number of skin lesions that subsequently developed. Ingenol mebutate treatment also significantly reduced the number of mutant p53 patches present in the skin.…”
Section: Introductionmentioning
confidence: 59%
“…This study thus illustrates that ingenol mebutate may find utility for the field-directed treatment of UV-damaged skin to reduce the emergence of AKs and NMSC. Such treatment may be particularly suitable for patients with multiple or recurring AKs (Berman et al, 2009;Jorizzo et al, 2010;Feldman and Fleischer, 2011) and/or patients who are at high risk of developing NMSC (Marcil and Stern, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Our expert panel concurred that AK is being increasingly perceived as a disease but thought that awareness of the risk of AK progressing into SCC is still lacking. Physicians' awareness of this therefore needs to increase, supporting the finding of another consensus study 28 that concluded the main treatment goal is to promote a good overall outlook by minimizing the risk of progression of AK to SCC. Developing physicians' knowledge of the potential for SCC to develop would provide them with the necessary background to promote and manage a successful treatment strategy that maximizes adherence and persistence.…”
Section: Ae Sdmentioning
confidence: 92%
“…AK evolves slowly in the basal layer until they become thicker and clinically evident as coarse erythematous patches in early stages; later they are hyperkeratotic [35]. Topical imiquimod 5% cream has been shown to be useful in clearing AK lesions [610]. Imiquimod as a toll-like-receptor-7- (TLR-7)-agonist induces cytokines, starting an inflammatory skin reaction directed primarily against malignant or virus-infected cells, but has virtually no effect on normal skin.…”
Section: Introductionmentioning
confidence: 99%